Fourteen-day vonoprazan-amoxicillin dual therapy versus 14-day bismuth-based quadruple therapy for treatment: a randomized clinical trial - Jin-Yan Zhang; Jin-Hai Chen; Yu-Lin Huang; Ji Li; Dong Xu; Zhong Xu; Xiao-Yi Lei (Therapeutic Advances in Gastroenterology)
Background: Potassium-competitive acid blockers (P-CABs) have shown potential in Helicobacter pylori ( H. pylori ) eradication, but the efficacy of dual therapy with P-CABs and amoxicillin remains underexplored. Objectives: This study evaluated the efficacy, safety, and compliance of a 14-day vonoprazan-amoxicillin (VA) dual therapy compared to a bismuth-based quadruple therapy (BQT) in treatment-naive patients. Design: A randomized clinical trial. Methods: This single-center, prospective, randomized controlled trial enrolled 250 H. pylori -positive patients from November 2022 to April 2024. Participants were randomly assigned (1:1) to receive 14-day VA dual therapy or BQT (lansoprazole, bismuth, amoxicillin, and clarithromycin). The primary outcomes were eradication rates in intention-to-treat (ITT) and per-protocol (PP) analyses. Secondary outcomes included adverse events and treatment compliance. Results: Eradication rates in the ITT analysis were 92.0% for the VA dual group and 88.0% for the BQT group ( p  = 0.292). In the PP analysis, eradication rates were 95.8% and 91.7%, respectively ( p  = 0.188). The VA dual group demonstrated statistically significant non-inferiority to the BQT group in both the ITT and PP analyses (both p  < 0.001). The incidence of adverse events was significantly lower in the VA dual group compared to the BQT group (11.2% vs 20.8%, p  = 0.038), with no severe adverse events reported. The compliance rates of both groups were 97.6%. Conclusion: The 14-day VA dual therapy is highly effective and well-tolerated, demonstrating non-inferiority to BQT. Given its reduced antibiotic usage and lower adverse events, it may be a viable first-line alternative for H. pylori in southern China. Trial registration: This trial was registered on the Chinese Clinical Trial Registry with the registration number ChiCTR2200055752.